Soluble Fibrin Monomer Complexes Demonstrated by Agarose Gel Filtration and by Adsorption on Insolubilized Fibrinogen - von Hugo, R; Hafter, R; Stemberger, A; Graeff, H (Thrombosis and Haemostasis, 1975)
Incubation of fibrinogen with small amounts of thrombin resulted in the occurrence of soluble fibrin monomer complexes. These complexes consisted predominantly of a derivative with a higher molecular weight than that of fibrinogen. It was characterized by its relative electrophoretic mobility in 5% PAA gel (0.28 × 10-5 cm2/V × sec) and its elution position prior to the fibrinogen peak following gel filtration. Using adsorption chromatography on insolubilized fibrinogen the derivative dissociated at a ratio of almost 1 : 1 into one part which was adsorbed and into fibrinogen which was not adsorbed. The part which was adsorbed seemed to be the thrombin mediated fibrin monomer. This study confirms the concept that dissociable dimeric fibrinogen-fibrin monomer complexes occur after limited action of thrombin on fibrinogen.